Impact of test-and-treat and risk reduction strategies on HCV transmission among MSM living with HIV in France: a modelling approach. Issue 8 (27th October 2020) - Castry, Mathieu; Cousien, Anthony; Supervie, Virginie; Velter, Annie; Ghosn, Jade; Paltiel, A David; Yazdanpanah, Yazdan; Deuffic-Burban, Sylvie
Abstract : Objective: Since the early 2000s, there has been an epidemic of HCV occurring among men who have sex with men (MSM) living with HIV, mainly associated with high-risk sexual and drug-related behaviours. Early HCV diagnosis and treatment, and behavioural risk-reduction, may be effective to eliminate HCV among MSM living with HIV. Design: We developed a deterministic dynamic compartmental model to simulate the impact of test-and-treat and risk-reduction strategies on HCV epidemic (particularly on incidence and prevalence) among MSM living with HIV in France. We accounted for HIV and HCV cascades of care, HCV natural history and heterogeneity in HCV risk behaviours. The model was calibrated to primary HCV incidence observed between 2014 and 2017 among MSM living with HIV in care (ANRS CO4-French hospital database on HIV (FHDH)). Results: With current French practices (annual HCV screening and immediate treatment), total HCV incidence would fall by 70%, from 0.82/100 person-years in 2015 to 0.24/100 person-years in 2030. It would decrease to 0.19/100 person-years in 2030 with more frequent screening and to 0.19 (0.12)/100 person-years in 2030 with a 20% (50%) risk-reduction. When combining screening every 3 months with a 50% risk-reduction, HCV incidence would be 0.11/100 person-years in 2030, allowing to get close to the WHO target (90% reduction from 2015 to 2030). Similarly, HCV prevalence would decrease from 2.79% in 2015 to 0.48% in 2030 (vs 0.71% with current practices). Conclusion: Combining test-and-treat and risk-reduction strategies could have a marked impact on the HCV epidemic, paving the way to HCV elimination among MSM living with HIV.